Community Structure and Distribution of Coleoptera Soil IPM and Non IPM Upland Vegetable Agricultural Areas in Two Villages in Kabanjahe - Arlen Hanel John (Talenta Publisher, 2021)
The concept of Integrated Pest Management (IPM) is an effort developed by the government in order to reduce the use of pesticides in the agricultural sector. In the development of agriculture in Kabanjahe, both Non-IPM (Non Integrated Pest Management) and IPM (Integrated Pest Management), research is needed to determine the community structure and distribution of soil fauna, including soil coleoptera, and to determine the effect of soil physical and chemical factors on soil coleoptera community structure in the highland vegetable farming area of Kabanjahe district. Karo Regency. Determination of sampling points in this study was carried out using the